KONTEKSTUALITAS TAFSIR AL-MIZAN FI TAFSIR AL-QUR'AN KARYA SAYYID MUHAMMAD HUSAIN TABATABA'I - Fauzul Iman (Al Qalam, 2014)
Mizan exegesis is a set of book explained many different aspects such as worship, legal social, history, philosophy, and political leadership. Each of this topic described based on contextual approach and methodology. The author of this book attempted to respond the social phenomenon that developed from materialism of western scholarship. Within this problem, this essay will answer the following main questions: to what extent does Al Mizan has a contextual legal implication toward usury?. How does Al-Mizan contextualize the marriage verses, slavery, and politics (siyasah Syar'iyyah)? This research is library research that is qualitative, and to analyze the data there are methods that will be employed such as ijmali, tahlili, muwarran (comparative), and maudhui.The conclusion notified that the usury prohibition implied social problem among people, the one who gets benefits and the other doesn't get any, this problem arise a social enry, therefore usury is prohibited. The verses related to marriage lies on the problem of polygamy, those verses contextualized that it is allowed yet must be founded by fairness. Third, the author's of Al-Mizan explained that slavery verses goes along with the prohibition of human slavery, because all human being must treated equally, and the last the politics contextualized with the obligation of obeying the leader in many ways.Keywords: exegesis, contextuality, Tabatabia'i